Diabetes Self-management Training in a Virtual Environment. (August 2017) - Reagan, Louise; Pereira, Katherine; Jefferson, Vanessa; Evans Kreider, Kathryn; Totten, Susan; D'Eramo Melkus, Gail; Johnson, Constance; Vorderstrasse, Allison
Diabetes self-management training (DSMT) improves diabetes health outcomes. However, low numbers of patients receive DSMT. Using virtual environments (VEs) for DSMT is an innovative approach to removing barriers for patients. The purpose of this paper is to describe the experience of health professionals and diabetes educators establishing and teaching DSMT in a VE, Diabetes LIVE© (Learning in Virtual Environments), and the implications for future use of VEs in DSMT. It was found that providing DSMT in a VE preserves real-time interaction between patients and educators. To facilitate ongoing patient learning and engagement, the DSMT curriculum was expanded beyond the core content as "Above and Beyond" topics. Using a VE for DSMT presents challenges and opportunities. Challenges include overcoming technological barriers and improving comfort levels to orient educators and patients to the functionality of the VE. Opportunities include overcoming barriers to reaching patients, particularly given the diabetes epidemic and relatively small number of diabetes educators. Using a VE also affords a simulated community for experiential learning. VEs may become powerful tools for diabetes and other health educators to reach patients. Ongoing education and support are vital to successful self-management of chronic disease.